Effect of Incorporation of Rice Husk Ash Instead of Cement on the Performance of Steel Fibers Reinforced Concrete - Zaid, Osama; Ahmad, Jawad; Siddique, Muhammad Shahid; Aslam, Fahid (Frontiers in Materials, 2021)
The Production of rice is significant worldwide; the husk produced is generally used as combustible material in the furnace for the preparation of paddy, delivering energy through direct combustion as well as by gasifying. The annual production of Rice Husk Ash (RHA) is 7.4 million tons and is an incredible danger to the environment, making harm to the land and the encompassing zone wherein it is unloaded. In the transformation of rice husk to ash, the ignition cycle eliminates the natural products leaving silica-rich remains. These silica-rich remains have proven potential to be utilized in concrete as a limited substitution of cement to enhance the concrete compressive strength. Steel fibers incorporation increases the concrete tensile strength balanced out concrete samples and changes their brittle behavior to the ductile response. In the current study, the influence of various doses of Rice Husk Ash (RHA) used in concrete in the presence and absence of steel fibers and concrete performance has been examined. A total of nine mixes have been designed, one of them was control, the rest four were without steel fibers containing only RHA, the last four mixed contains RHA as well as steel fibers from 0.5% to 2%. Tests with 5%, 10%, 15%, and 20% percentages of RHA replacing the concrete have been targeted. Results have been compared with the reference samples and the reasonability of adding Rice Husk Ash to concrete has been studied. From the results, it was noted that about 10% of cement might be replaced with Rice Husk Ash mixed in with steel fibers with almost equal compressive strength. Replacing more than 15% of cement with RHA will make concrete which will have low performance in terms of strength and durability.